Vpliv odprtega dostopa na časovni odmev objav - Koler-Povh, Teja (Organizacija znanja, 2017)
The open access as a new bussiness model in scientific communication can have an impact on citations of scientific publications, which has been researched a lot. This article presents an analysis of the echo time, which indicates the period from publishing an article to the time of its first citation. The analysis of the echo time was made in two phases. In the first phase we selected four most frequently cited internationally renowned journals in civil engineering, ranked in the upper half of the JCR (Journal Citation Reports) list. In the second phase we investigated, for these journals, the number of citations by year in the period from their publication in 2007 till the end of 2012 in the following three databases: Web of Science (WoS), Scopus and Google Scholar (GS). They are hybrid journals, in which open access (OA) and non-open access (NOA) articles are published. In the study it was established that the first citations of OA and NOA articles appeared in the first year after publishing, but, on average, in first year after publication, more citations of OA articles appeared than of NOA articles. Both, OA and NOA articles published in the examined journals, reached the highest number of citations in the third or fourth year after publication regarding the indicator average number of citations. Regarding the indicator proportion of the sum of the number of citations in the cumulative sum of the number of citations in the period 2007-2012 this happened even earlier, i.e. in the second or third year after publication. Trends for these two indicators show the possibility of one more culmination in the number of citations of OA and NOA articles, for many of them it will be reached at an even higher number of citations.
Keywords: časovni odmev; impact on citation; odprti dostop; open access; time echo; vpliv na citiranost